Analisa Simpang Tak Bersinyal (Studi Kasus Di Ruas Jalan Taman Simpang Kandis Kota Bengkulu) - Rima S; Endri Agustomi; Elly Tri Pujiastutie (MAJALAH TEKNIK SIMES, 2021)
Intersection are knots in transportation network where two or more roads meet, in this area conflict is occurred, law of traffic are applied to handle this conflict to make sure who gets the priority to use the intersection first. Control Intersection make use of maximum capacity of the intersection, reducing and preventing accidents by reducing the number of conflicts. This research intend to analyse the traffic and calculate traffic flow at Taman Simpang Kandis road. To get data for this research purpose can get done by using direct observation, and count number of vehicle that passed the four arms intersection and three arms intersection. The result of this survey categorized by light vehicle, heavy vehicle, motorcycle, and non-motorized vehicle. Four arms intersection performance analysed by observe capacity, saturation degree, delay, queue chance is still below the standard based on MKIJI 1997. The best alternative for the four arms intersection are by combining installation the “prohibited to stop“ road sign and change 2 lanes with 2 directions to four arms intersection with 2 lanes and 1 direction. Three arms intersection performance analysed by observe capacity, saturation degree, delay, queue chance is still below the standard based on MKIJI 1997. The best alternative for this three arms intersection are by prohibited to turn left from Rustandi Sugianto 1 road and prohibited to turn right form Rustandi Sugianto 2 road where can make vehicle stacked on side of that road.